PENGARUH STRESOR PSIKOLOGIK TERHADAP DISTRIBUSI TRANSPORTER SEROTONIN (SERT) DAN INDEKS APOPTOSIS HIPOKAMPUS YANG DIMEDIASI OLEH KORTISOL DAN IL – 6 - Suparno, Suparno (Fakultas Kedokteran Universitas Brawijaya, 2007)
Generally, distress which followed by psychiatric disorders still become a medicinal practice controversial especially psychologically stressor roles on holistic health condition. Therefore, research is needed to explain and clarify the influences and the role of psychologically stressors on psychiatric disorders. This study used an psychoneuroimmunologic paradigm, which used posttest-only true experiment design. About 24 female Rattus norvegicus strain Wistar had been used, divided into six groups. To investigate functional changes, we used hippocampus SERT distribution changes as mirror of central serotonergic malfunction changes.The structural changes was measured by apoptosis index of hippocampus CA3 regions (hippocampus slicing). We also took the blood from the rats heart to examine IL ? 6 and cortisol level. Psychological stressors lead to measuring of functional and structural changes include hippocampus SERT distribution and increase hippocampus apoptotic index, that finally arise the distress.These results of statistical analyses demonstrate that psychological stressors seem to be mediated by serotonergic neurotransmission pathway. Key words :hippocampus CA3 region, SERT malfunction, IL-6, cortisol, psychological stressors